Studi Karakterisasi dan Aktivitas Antibakteri Senyawa Kompleks dari Zink(II) Klorida, Kalium Tiosianat dan 2-Aminopiridina - Mariyam, Dewi; Farida, Nani; Wijaya, Husni Wahyu; Dasna, I Wayan (Jurnal Riset Kimia, 2022)
The development of complex compounds as antibacterial continues to be carried out to overcome cases of microbial resistance. One of them is the development of complex compounds with thiocyanate and aminopyridine ligands which show good potential as antibacterial. Complex compound of zinc(II) chloride with thiocyanate and 2-aminopyridine ligands was successfully synthesized. The synthesis was carried out by mixing the reactants with ratio of Zn2+: 2-aminopyridine: SCN 1:2:2 under heating and stirring continuously for 6 hours. The Obtained beam-shaped colorless crystals were characterized using melting point, electrical conductivity, thiocyanate ion qualitative, FTIR, SEM-EDX, XRD powder and antibacterial activity against Salmonella typhi and Staphylococcus aureus test. The crystals melt at 160-165 0C. The results of the electrical conductivity test, qualitative test of thiocyanate ion, FTIR and SEM-EDX analysis indicate the presence of Zn2+, thiocyanate and 2-aminopyridine with ratio 1: 2: 2. Based on XRD powder spectral data and theoritical analysis, the complex synthesized compounds had high crystallinity and predicted has tetrahedral structure. Antibacterial test showed that against S.aureus, the compound had higher antibacterial activity than free ligands, but lower than chloramphenicol. Therefore, the antibacterial activity of the complex compound was classified as moderate.